Gamification In Education: Designing A Basic Game Using Python's Turtle Graphics For Learning - Harmonvikler D. Lumban Raja (Universitas Advent Surya Nusantara, 2025)
In modern education, there is a growing need for innovative instructional methods that increase student engagement and facilitate the understanding of complex subjects such as programming. This study aims to design and evaluate a gamified educational game developed using Python’s Turtle Graphics, intended to enhance learning and motivation among novice programming students. Employing a mixed methods approach, the research combines empirical data collection from a purposive sample of first-year computer science students with descriptive statistical analysis of quantitative questionnaire results and thematic qualitative insights. The findings indicate that the gamified game effectively improves learners' comprehension of basic programming concepts while fostering sustained engagement and motivation. This study contributes novel empirical evidence demonstrating the viability of simple, accessible gamification tools in introductory programming education, offering practical implications for educators seeking to integrate technology-enhanced learning in foundational computer science curricula. The results underscore the role of gamification in supporting cognitive and motivational aspects of learning, advancing both theoretical understanding and classroom practice in educational technology.